KCNQ2 encephalopathy: Features, mutational hot spots, and ezogabine treatment of 11 patients. (October 2016) - Millichap, John J.; Park, Kristen L.; Tsuchida, Tammy; Ben-Zeev, Bruria; Carmant, Lionel; Flamini, Robert; Joshi, Nishtha; Levisohn, Paul M.; Marsh, Eric; Nangia, Srishti; Narayanan, Vinodh; Ortiz-Gonzalez, Xilma R.; et al.
Abstract : Objective: To advance the understanding of KCNQ2 encephalopathy genotype–phenotype relationships and to begin to assess the potential of selective KCNQ channel openers as targeted treatments. Methods: We retrospectively studied 23 patients with KCNQ2 encephalopathy, including 11 treated with ezogabine (EZO). We analyzed the genotype–phenotype relationships in these and 70 previously described patients. Results: The mean seizure onset age was 1.8 ± 1.6 (SD) days. Of the 20 EEGs obtained within a week of birth, 11 showed burst suppression. When new seizure types appeared in infancy (15 patients), the most common were epileptic spasms (n = 8). At last follow-up, seizures persisted in 9 patients. Development was delayed in all, severely in 14. The KCNQ2 variants identified introduced amino acid missense changes or, in one instance, a single residue deletion. They were clustered in 4 protein subdomains predicted to poison tetrameric channel functions. EZO use (assessed by the treating physicians and parents) was associated with improvement in seizures and/or development in 3 of the 4 treated before 6 months of age, and 2 of the 7 treated later; no serious side effects were observed. Conclusions: KCNQ2 variants cause neonatal-onset epileptic encephalopathy of widely varying severity. Pathogenic variants in epileptic encephalopathy are clustered in "hot spots" known to be critical for channel activity. For variants causing KCNQ2 channel loss of function, EZO appeared well tolerated and potentially beneficial against refractory seizures when started early. Larger, prospective studies are needed to enable better definition of prognostic categories and more robust testing of novel interventions. Classification of evidence: This study provides Class IV evidence that EZO is effective for refractory seizures in patients with epilepsy due to KCNQ2 encephalopathy.